The Impact of Using Gadgets at Early Age on The Brain Development of Infants and Children (Literature Review Article) - Erny Erny; Okky Prasetyo; Ayly Soekanto (Universitas Wijaya Kusuma Surabaya, 2022)
The use of gadgets is currently very evenly distributed in almost all age groups with screen times that are increasingly worrying, especially in infants and children. The influence of these devices can cause many problems not only social problems but especially health problems that have a long-term impact. Neuropsychiatric disorders caused by early use of gadgets in infants and children should be prevented by parents' understanding of the effects of using these devices. The purpose of writing this review article describes health problems that may arise due to the use of gadgets in children in an uncontrolled time. This literature review article was analyzed from 25 journals with topics of infant and toddler brain development, gadgets, electromagnetic waves and their impact on infant and toddler brain development. Search using pubmed central, google scholar, article in journals indexes Scopus Q1-4 and Sinta 1-4 from year 2002-2022. 25 journals were obtained and overall showed the impact of gadgets in the brain development.